Les mystères de Gilles de Rais Quelques mots sur la splendeur et la misère d’un transgresseur médiéval - Mrozowicki, Michał (Romanica Silesiana)
Gilles de Rais, the Marshal of France — who in 1429 fought beside Joan of Arc in some crucial campaigns during the Hundred Years War (such as the siege of Orléans) — after her burning at the stake in 1431, and after his maternal grand-father’s death the next year, became one of the most cruel and perverted serial murderers, pedophiles and necrophiles in the history of humanity. The paper describes this astonishing transformation that led him from the glorious military achievements to the stake after the controversial trial in Nantes in 1440. The article tries to answer the question if this transgressor (in the common sense of the word), who continues to fascinate people almost six centuries after his death, can also be considered a transgressor according to the criteria proposed by Józef Kozielecki, a Polish psychologist, and the father of psychotransgressionism. Key words: Transgression, Kozielecki’s psychotransgressionism, Gilles de Rais.